Public policies on entrepreneurship: An analysis of the brazilian legislative agenda between 2011 and 2024 - Paiva, Adaleny Dayanne Souza de; Pagotto, Daniel do Prado; Santos, Alef Oliveira dos; Rosim, Daniela (REGEPE Entrepreneurship and Small Business Journal, 2026)
Objective: To characterize the public policy proposals for entrepreneurship that were processed in the National Congress between 2011 and 2024. Methodology: The proposals were collected using the Selenium package in Python, then organized and classified by the authors according to types of public policy. Descriptive analyses were then performed based on the date of the proposal, its type, and the political party of the proposing representative. These elements were important for understanding how the themes evolved in different types, as well as among representatives across the political spectrum. Results: The results indicate that the period from 2019 to 2023 exhibits more proposals and that the themes most addressed by the authors of the policies were "target group measures" and "entry/exit barriers". The right wing has more legislators dealing with issues related to entrepreneurship, especially those related to "entry/exit barriers" and "financing". Theoretical/methodological contributions: The study highlights the use of data collection through web scraping and the classification of ongoing projects according to a typology of public entrepreneurship policies. Relevance/originality: Provide evidence on the early stages of public policy formulation, filling a gap in the literature. Social/management contributions: Point out that most policies focus on reactive measures to meet the demands of specific groups, rather than on actions that can generate long-term competitive conditions, such as innovation and infrastructure.